Professional exercise of nursing and the implications for the performance on mental health and psychiatry - Torres Pique, Ana María; Pontificia Universidad Javeriana (Pontificia Universidad Javeriana - Facultad de Enfermería, 2011)
This situation of mental health of the population in the world and in Colombia, raises great challenges and responsibilities to the nursing professional who as a natural caretaker of health and life, is a main resource for providing restorative help that allows persons, groups and communities to reach integrative wellbeing. The tendencies in health for the next years force us to rethink nursing education and nursing professional roles in order to be able to respond, in a humanistic form to the complex nursing care necessities on mental health and psychiatry.